Chloride Penetration through Cracks in High-Performance Concrete and Surface Treatment System for Crack Healing. (2nd April 2012) - Yoon, In-Seok
Abstract : For enhancing the service life of concrete structures, it is very important to minimize crack at surface. Even if these cracks are very small, the problem is to which extend these cracks may jeopardize the durability of these decks. It was proposed that crack depth corresponding with critical crack width from the surface is a crucial factor in view of durability design of concrete structures. It was necessary to deal with chloride penetration through microcracks characterized with the mixing features of concrete. This study is devoted to examine the effect of high strength concrete and reinforcement of steel fiber on chloride penetration through cracks. High strength concrete is regarded as an excellent barrier to resist chloride penetration. However, durability performance of cracked high strength concrete was reduced seriously up to that of ordinary cracked concrete. Steel fiber reinforcement is effective to reduce chloride penetration through cracks because steel fiber reinforcement can lead to reduce crack depth significantly. Meanwhile, surface treatment systems are put on the surface of the concrete in order to seal the concrete. The key-issue is to which extend a sealing is able to ensure that chloride-induced corrosion can be prevented. As a result, penetrant cannot cure cracks, however, coating and combined treatment can prevent chloride from flowing in concrete with maximum crack width of 0.06 mm and 0.08 mm, respectively.